Inhibitory Control of Spanish-Speaking Language-Minority Preschool Children: Measurement and Association With Language, Literacy, and Math Skills. (July 2017) - Lonigan, Christopher J.; Allan, Darcey M.; Goodrich, J. Marc; Farrington, Amber L.; Phillips, Beth M.
Children's self-regulation, including components of executive function such as inhibitory control, is related concurrently and longitudinally with elementary school children's reading and math abilities. Although several recent studies have examined links between preschool children's self-regulation or executive function and their academic skill development, few included large numbers of Spanish-speaking language-minority children. Among the fastest growing segments of the U.S. school-age population, many of these children are at significant risk of academic difficulties. We examined the relations between inhibitory control and academic skills in a sample containing a large number of Spanish-speaking preschoolers. Overall, the children demonstrated substantial academic risk based on preschool-entry vocabulary scores in the below-average range. Children completed assessments of language, literacy, and math skills in English and Spanish, when appropriate, at the start and end of their preschool year, along with a measure of inhibitory control, the Head-Toes-Knees-Shoulders task, which was administered at the start of the preschool year in the child's dominant conversational language. Scores on this last measure were lower for children for whom it was administered in Spanish. For both English and Spanish outcomes, those scores were significantly and uniquely associated with higher scores on measures of phonological awareness and math skills but not vocabulary or print knowledge skills.